Uncertainty of Sanction Norms in Safeguarding Political Rights of Disabled Voters in Indonesia - I Kadek Achmad Ricardo Riyan Saputra; Satrio Prawirajaya; Rangga Putra Adinata; Fitria Damayanti; Azwar Siri (Universitas Negeri Surabaya, 2026)
The protection of political rights is a fundamental element of democratic governance and reflects the principle of equality before the law. Within a democratic framework, all citizens are entitled to engage in political processes without discriminatory barriers, including individuals with disabilities. Their involvement may take multiple forms throughout the electoral process, whether as voters, electoral candidates, or contributors to the administration of elections. Although these rights have been formally recognized within the national legal framework, their effective implementation in practice continues to encounter various challenges. Significant challenges persist, especially in guaranteeing adequate accessibility throughout the electoral process. This study contributes to the debate on legal certainty by examining sanction norms within the hierarchy of laws and regulations governing disability rights in elections. The analysis focuses on the relationship between general guarantees of disability rights, the broader legal framework governing elections, and technical administrative guidelines developed by electoral institutions. Using normative legal research with statutory and conceptual approaches, the study finds that although the regulatory structure appears formally aligned, the provisions concerning sanctions remain general and lack clarity. This condition weakens the effectiveness of legal protection and may hinder the realization of accessible and inclusive elections for persons with disabilities.